2016
DOI: 10.1080/15226514.2016.1146227
|View full text |Cite
|
Sign up to set email alerts
|

Some adverse effects of soil amendment with organic Materials—The case of soils polluted by copper industry phytostabilized with red fescue

Abstract: The study was aimed to examine the effects of soil amendment with organic waste materials on the growth of red fescue and the uptake of Cu and Zn by this grass, in view of its potential usage for phytostabilization of Cu-polluted soils. Five soils, containing 301-5180 mg/kg Cu, were collected from the surroundings of copper smelter Legnica, and amended with lignite (LG) and limed sewage sludge (SS). Plant growth and the concentrations of Cu and Zn in the shoots and roots of grass were measured in a pot experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…For instance, technosols manufactured with primary paper sludge have higher pH and hence results in lower shoot biomass than do technosols manufactured using woody residuals (Watkinson et al 2017). Similarly, the application of alkaline sewage sludge can result in dramatic increase of Cu phytotoxicity and enhanced uptake of Cu by red fescue (Cuske et al 2016). Biochar, a low-density carbon-rich material produced by pyrolysis of plant biomass at temperatures of 300-1000°C, has gained increasing attention recently as soil amendment Park et al 2011;Zhang et al 2012).…”
Section: Physical Methodsmentioning
confidence: 99%
“…For instance, technosols manufactured with primary paper sludge have higher pH and hence results in lower shoot biomass than do technosols manufactured using woody residuals (Watkinson et al 2017). Similarly, the application of alkaline sewage sludge can result in dramatic increase of Cu phytotoxicity and enhanced uptake of Cu by red fescue (Cuske et al 2016). Biochar, a low-density carbon-rich material produced by pyrolysis of plant biomass at temperatures of 300-1000°C, has gained increasing attention recently as soil amendment Park et al 2011;Zhang et al 2012).…”
Section: Physical Methodsmentioning
confidence: 99%
“…A similar analysis based on the data from later stages of incubation (not shown in this paper) [21], indicated that the character of relationships between the main factors that governed metals solubility changed noticeably and became much more similar to the relationships presented for non-amended soils. This fact clearly corresponds with the aging of contaminants, i.e., the effects described earlier.…”
Section: +2mentioning
confidence: 74%
“…A similar effect of Cu dilution was observed in SS-amended soils, while Zn concentrations in soil Nos. 2-5 increased slightly, as SS was rich in Zn [21]. This increase may, however, be considered negligible.…”
Section: The Properties Of Soils and Organic Amendmentsmentioning
confidence: 99%
“…Soil solutions were obtained repeatedly in 1, 2, 7, 14, and 30 days of incubation using MacroRhizon samplers. The concentrations of copper and other major components of soil solutions, including dissolved organic carbon DOC as well as pH, were determined by the methods described by Cuske et al [15]. The toxicity of soil solutions was measured using two tests: a Microtox assay based on inhibition of Vibrio fischeri bioluminescence, and a Phytotoxkit assay based on inhibition of seed germination and root and shoot elongation, carried out with Sinapis alba.…”
Section: Methodsmentioning
confidence: 99%
“…Soil material was air dried, sieved, homogenized, and mixed with a beech litter (BL) obtained from an uncontaminated area. Basic properties of soils and litter were determined using the methods described by Tan [14] and reported in more detail elsewhere [15].…”
Section: Methodsmentioning
confidence: 99%